Clinical Review: Familial Mediterranean Fever—An Overview of Pathogenesis, Symptoms, Ocular Manifestations, and Treatment. (3rd July 2016) - Petrushkin, Harry; Stanford, Miles; Fortune, Farida; Jawad, Ali S.
Abstract: Familial Mediterranean fever is an autoinflammatory multisystem disease, which most commonly affects patients from the Mediterranean basin. This review discusses the common polymorphisms in the MEFV gene as well as the role of pyrin in disease pathogenesis. Patients with familial Mediterranean fever typically develop peritonitis, pleuritis, arthritis, and fever. In addition, a number of authors have reported ophthalmic features. These case reports and series are further explored in this review. Colchicine has transformed the prognosis for patients with familial Mediterranean fever. The rationale for the use of colchicine, as well as the evidence for newer biologic agents is also covered.